Desafios na concretização do direito à educação em Fortaleza: uma análise do acesso à creche entre 2007 e 2022 - Oliveira, Bruno de Sousa (2023)
The present study seeks to investigate the challenges that face the operation of daycare centers as public policies in the city of Fortaleza-CE, whereas the right to daycare is a fundamental right and its implementation necessarily depends on state action. The research is based on a theoretical understanding that the fundamental right to daycare has essential content with broad factual support, which means going beyond access. Despite this, and considering the history of insufficient places in daycare centers in Brazil and in Fortaleza, the data collection in this work focused on the access dimension, as well as in the investigation of public financing, in Fortaleza-CE from 2007 to 2022. The theoretical discussion on the right to quality in education, applied to the daycare stage, as well as the methodological approach to Law and Public Policies were used as the basis for the investigation. Based on the compiled data, it was possible to observe an expansion of the public daycare network in Fortaleza over the last 16 years, a period that coincides with the establishment of the national Fundo de ManutenÁ„o e Desenvolvimento da EducaÁ„o B·sica e ValorizaÁ„o dos Profissionais da EducaÁ„o (FUNDEB). For the most part, this expansion was directed to regions of the city with the lowest Human Development Index (IDH) and was based on the expansion of its own network, without the prevalence of the partnership model with civil society organizations. Although the Day Care Attendance Rate has grown in Fortaleza-CE in the period from 2007 to 2022, the most recent index indicates an impossibility of achieving the goals set out in the National Education Plan and the Municipal Education Plan. The last few years of analysis also recorded the largest number of children who sought public daycare centers and were unable to find places, despite the growth observed in the period. The study brings elements for the critical analysis of state action in Fortaleza-CE, pointing out the main challenges in accomplishing this right in the analyzed period and in its future implementation. Finally, based on the chosen methodology, it is pointed out that this research could be replicated in future studies and in the analysis of other entities.